PENGEMBANGAN BAHAN AJAR ASESMEN PERKEMBANGAN ANAK USIA DINI DENGAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PBL) - Hardiyanti Pratiwi (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2020)
This study aims to develop teaching materials for the assessment of early childhood development using the Dick and Carey development model. This is because given the importance of assessment and evaluation to support and ensure the successful development of all potential early childhood, PAUD teachers and parents must acquire this expertise as possible. However, learning that only focuses on understanding theory without being accompanied by practice is the main cause of PIAUD students not having the skills in designing instruments and carrying out assessments. The data source in this study is 2017 PIAUD students as prospective users and expert validators, consisting of material experts and learning design experts. The product trial design consists of expert validation, individual trials, and small group trials. The trial results show: (1) The questionnaire from the expert validator stated that there were no indicators that needed to be revised, but there were a number of notes from experts outside the indicators in the questionnaire, so the researcher made a revision of the notes. (2) There are several suggestions and input from individual trial respondents, amounting to 3 people. Furthermore, the revised results of individual trials were retried on small groups. (3) In the small group trial there are also some notes / suggestions from respondents which are used as a guide for researchers to revise teaching materials in the final stage.